Dosimetric impact of rotational setup errors in volumetric modulated arc therapy for postoperative cervical cancer. (29th May 2021) - Tsujii, Katsutomo; Ueda, Yoshihiro; Isono, Masaru; Miyazaki, Masayoshi; Teshima, Teruki; Koizumi, Masahiko
Abstract: We aimed to evaluate the impact of rotational setup errors on the doses received during postoperative volumetric-modulated arc therapy (VMAT) for cervical cancer. Overall, 121 cone-beam computed tomography (CBCT) sets from 20 patients were rigidly registered to reference computed tomography (CT) sets based on bony landmarks. The rotational setup errors (pitch, yaw and roll) were calculated. Then, 121 CT sets involving rotational setup errors were created, and the dose distribution in these CT sets were recalculated. The recalculated dosimetric parameters for the clinical target volume (CTV) and organs at risk (OAR) were compared to the reference values, and the correlation coefficients between the dosimetric parameter differences and rotational setup errors were calculated. Only the pitch setup error was moderately correlated with CTV coverage (r ≥ 0.40) and strongly correlated with V45 for the bladder (r ≥ 0.91) and V40 for the rectum, small bowel and bone marrow (r ≥ 0.91). The maximum dosimetric difference in a single fraction and overall fractions was −1.59% and −0.69% in D98 for the CTV, 11.72% and 5.17% in V45 for the bladder and −8.03% and −4.68% in V40 for the rectum, respectively. In conclusion, rotational setup errors only slightly impact dose coverage during postoperative cervical cancer VMAT. However, the pitch setup error occasionally affected the doses received by the bladder or the rectum in the overall fraction when the error was systematic. Thus, rotational setup errors should be corrected by adjusting six-degree-of-freedom (DOF) couches to reduce dosimetric differences in the OARs.